2014
DOI: 10.1158/1078-0432.ccr-14-0007
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Angiopoietin-like Protein 2 Correlates with the Metastatic Properties of Colorectal Cancer: A Serum Biomarker for Early Diagnosis and Recurrence

Abstract: Purpose: Angiopoietin-like protein 2 (ANGPTL2) is a mediator of chronic inflammation and inflammatory carcinogenesis. The biologic and clinical significance of ANGPTL2 remains unknown in human cancer. Therefore, we investigated the function of ANGPTL2 and evaluated its clinical significance in both primary tumors and matched sera in patients with colorectal cancer.Experimental Design: A colorectal cancer cell line was transfected with siRNA against ANGPTL2 for the assessment of its function. We examined ANGPTL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Further intervention studies show that targeted inhibition of Ang2 can inhibit tumor angiogenesis and lymphangiogenesis. Therefore, Ang2 may be the potential target for anticancer therapy . By performing luciferase reporter gene assay and western blot, this study confirmed the regulatory ability of miR‐93 on Ang2 expression on both molecular level and protein level.…”
Section: Discussionsupporting
confidence: 64%
“…Further intervention studies show that targeted inhibition of Ang2 can inhibit tumor angiogenesis and lymphangiogenesis. Therefore, Ang2 may be the potential target for anticancer therapy . By performing luciferase reporter gene assay and western blot, this study confirmed the regulatory ability of miR‐93 on Ang2 expression on both molecular level and protein level.…”
Section: Discussionsupporting
confidence: 64%
“…KRAS (exons 2 and 3) and BRAF (V600E) mutations were analyzed by pyrosequencing as previously described (26). The list of primers used is found in Supplementary Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…29 Circulating ANGPTL2 levels increase with age in Japanese populations 25 and are high in patients with chronic, age-associated diseases, such as heart disease, kidney disease, diabetes, and cancer. 21,29- 35 Previous studies have shown that ANGPTL2 potently promotes pro-angiogenic and anti-apoptotic activities, as do the ANGPTs. 28,36,37 Moreover, we reported that ANGPTL2 signaling through integrin α5β1 enhances cell motility by activating the Rho family GTPase Rac1 and by stimulating remodeling of the extracellular matrix (ECM) through activation of p38 mitogen-activated protein kinase (MAPK)-dependent matrix metalloproteinases (MMPs) (Figure 1).…”
Section: Angptl2 Function In Cvd Development and Progressionmentioning
confidence: 99%
“…As noted earlier, circulating ANGPTL2 levels increase with age in Japanese populations 25 and are high in patients with chronic, age-associated diseases such as heart disease, kidney disease, diabetes, and cancer. 21,29- 35 Thus, ANGPTL2 may function as a SASP in several senescent cell types. If so, markedly increased circulating ANGPTL2 levels seen in patients with chronic aging-related diseases may reflect the accumulation of senescent cells in their organs.…”
Section: Angptl2 Expression Is Associated With Cellular Senescencementioning
confidence: 99%